The Effect of Hyperbaric Oxygen in Reducing Blood Cortisol Levels in Patients with Sleep Disorders - I Ketut Tirka Nandaka; Hisnindarsyah Hisnindarsyah; Saptono Putro (Jurnal Indonesia Sosial Sains, 2024)
Sleep disorders disrupt normal sleep patterns, including timing, duration, and quality, often linked to elevated cortisol levels and high nerve metabolism requiring oxygen. Hyperbaric oxygen therapy (HBO), delivering pure oxygen in high-pressure settings (≥1.4 ATA), may alleviate hypoxia and reduce cortisol, offering potential treatment for sleep disorders. This research uses a quasi-experimental design with a randomized pre-post control group design. The population studied was male sleep disorder sufferers, aged 25-40 years at the psychiatric poly of Dr. Ramelan Surabaya Hospital, with a sample of 9 members of the Indonesian Navy who met the inclusion and exclusion criteria. This research is related to development research in the field of health and maritime, with a focus on diving and hyperbaric oxygen therapy, which is expected to be published in the International Journal indexed Shinta 2. This research has the potential to enrich the understanding of the effects of Oxygen Hyperbaric (OHB) therapy in overcoming sleep disorders, as well as contributing to the health and maritime sectors. The research concluded that OHB therapy in sleep disorder patients resulted in a slight reduction in mean cortisol levels (from 79.09 ng/ml to 76.38 ng/ml). Although the majority of patients (56%) experienced a decrease in cortisol levels after therapy, there was no statistically significant effect of OHB therapy on cortisol levels in sleep disorder patients.